Pregnancy and Oral Health: Importance of dental prenatal care (Research, Society and Development, 2021)
This paper aims to present common dental problems during pregnancy, as well as dental management during this period. This study consists of a qualitative bibliographic review, using Scielo, BVS, and Pubmed as the source of data chosen for research. Presenting a selective proposal for the election of the studies chosen for this work, where the selection criteria were: research of articles from 2010 to 2020, Portuguese, English, and Spanish, which address descriptors such as and / or related to: pregnant women, oral health , prenatal care, oral health, pregnancy, pregnant women, primary health care, el embarazo, odontológica. Dental prenatal care should start as soon as the pregnancy is discovered, however, the ideal would be the occurrence of planning prior to pregnancy, so that the adequacy and promotion of oral health would occur, since adverse results are observed in pregnancies that mother is in terrible oral conditions, where the prevention / treatment of oral problems before the start of pregnancy would be synonymous with an even healthier pregnancy, both for the mother and the child. The dental surgeon would observe the entire state of oral health of the pregnant woman, which makes it possible to prevent aggravations of installed oral problems, and to prevent new changes.